21C credentials : final report 2016 of OLT strategic priority project : curate, credential and carry forward digital learning evidence. - Oliver, Beverley (Office for Learning and Teaching, 2016)
This project proposed to connect Australian higher education providers with national and international networks of innovators and scholars in emerging practices in digital curation and credentialling - that is, conferring macro and micro credentials based on evidence of learning richer than codified marks, grades and credits. This two-year project proposed to deliver five outcomes: (1) connect Australian higher education providers with national and international networks of innovators and scholars in digital curation and credentialling of rich learning evidence, and its portability across educational sectors; (2) research and publish analysis and commentary on the implications for emerging business models in compliance with higher education standards and regulatory frameworks; and student, employer and provider insights into the practical usefulness, usability and portability of emerging micro credentials; (3) provide advice, in the form of case studies and a good practice guide to inform implementation; (4) offer professional development for higher education practitioners through curation and credentialling of their own learning evidence; and (5) host a national forum, with webcast access for all Australian providers, inviting high profile international and national thought-leaders to share their experiences and reflections on the implications of curating, credentialling and carrying forward evidence of learning. This report details the key achievements of the five intended outcomes. [VOCED]